2017
DOI: 10.1007/s40843-017-9083-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel lithium-ion battery comprising Li-rich@Cr2O5 composite cathode and Li4Ti5O12 anode with controllable coulombic efficiency

Abstract: Through meticulous design, a Li-lacking Cr

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Choosing a proper anode plays a major role in improving the ICE of an LRM full cell. Ding et al [183] suggested that the LRM@ Cr 2 O 5 ||Li 4 Ti 5 O 12 full cell exhibited higher ICE (97.7%) than the LRM@Cr 2 O 5 //graphite counterpart (71.8%). Si-based materials are considered candidates for pairing with LRMs owing to their high capacity.…”
Section: The Practical Application Progress Of Lrm Cathodes In Full Cellmentioning
confidence: 99%
“…Choosing a proper anode plays a major role in improving the ICE of an LRM full cell. Ding et al [183] suggested that the LRM@ Cr 2 O 5 ||Li 4 Ti 5 O 12 full cell exhibited higher ICE (97.7%) than the LRM@Cr 2 O 5 //graphite counterpart (71.8%). Si-based materials are considered candidates for pairing with LRMs owing to their high capacity.…”
Section: The Practical Application Progress Of Lrm Cathodes In Full Cellmentioning
confidence: 99%
“…Other innovative approaches.-Except for these basic and common strategies, researchers have found many other innovative approaches. 160 The following lists three more distinctive methods.…”
Section: Strategies For High Rate Capacity Performance Improvementmentioning
confidence: 99%